"Don't play with God!": Black Church, Play, and Possibilities. Issue 2 (1st October 2016) - Smith-Shomade, Beretta E.
Abstract : This article looks at black church through the framework of playful piety—its aesthetic forms and expressive culture. Specifically, I interrogate how Issa Rae's Mis-Adventures of Awkward Black Girl web series, entertainer Rickey Smiley, and the Preachers of LA reality television series mix black religiosity and humor. These pop cultural forms and forums serve as a venue for Black folks to not only see themselves enacted religiously but also to enjoy the foibles, fallacies, contributions, and even grace of black religious ways of being.